The influence of vegetation cover on the grain-size distributions and thicknesses of two Icelandic tephra layers - Conner Morison; Richard Streeter (Volcanica, 2022)
Grain-size distributions and thicknesses of tephra layers are used to reconstruct characteristics, dynamics, and hazards of explosive volcanic eruptions, but the extent to which the preservation of tephra is in uenced by depositional environments is unclear. This paper analyses grain-size distributions and thicknesses of tephra layers produced by the Eyjafjallajökull (2010) and Grímsvötn (2011) eruptions. We collected 110 tephra samples and layer thickness measurements from 86 sites at two locations in southern Iceland. Areas of different vegetation cover have varying capacities to affect rates of tephra erosion, retain fallout, or capture remobilised tephra. The Grímsvötn tephra was somewhat coarser-grained and thicker in areas of birch woodland than in adjacent moss heath, but no comparable differences in the Eyjafjallajökull tephra were observed. The spatial variability (over tens of metres) of median particle-size and layer thickness is low, providing con dence that relatively few samples and measurements may be required to capture fallout characteristics.